Outcome of Vitrectomy Surgery in Dropped Nucleus at Jakarta Eye Center - Referano Agustiawan; Elvioza Elvioza; Soedarman Sjamsoe; Waldensius Girsang (Indonesian Vitreoretinal Society, 2018)
Introduction: To report management and outcome of dropped nucleus in Jakarta Eye Center Methods: Retrospective review of the records of 19 consecutive patients who underwent pars plana vitrectomy for retain lens fragments at Jakarta Eye Center from January 2010 to September 2012. Result: The mean age of the patient was 57 years (range 48-79). There were 10 males (53%) and 9 females (47%). 10 patients (53%) had vitrectomy within 1 day of phacoemulsification, 6(32%) within 1 week and 3(15%) after more than 1 week. Eight patients (42%) achieved a final visual acuity of 0.5 or better, only 3 patients (15%) had final visual acuity 1-meter finger counting or worse. 74% patient achieved final acuity better than pre-op (14 patients). Early vitrectomy group has 3 patients (30%) with complication, intermediate vitrectomy group has 33% complication and late vitrectomy has 33 % complication. Posterior chamber IOL were implanted in 12 patients (63%), 2 patients had scleral fixation IOL, anterior chamber IOL in 2 patients, and only 3 patients (16%) were left aphakic. Conclusion: Surgical management in cases of nucleus drop in JEC showed good result with very limited complications. In most cases, vitrectomy was performed immediately after cataract surgery. Early vitrectomy has no significant differences in complications and visual outcome than 1 week vitrectomy and late vitrectomy after cataract surgery.